2020
DOI: 10.1038/s41423-020-0515-7
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Vγ9Vδ2 T-cell immunotherapy exhibits promising clinical safety and prolongs the survival of patients with late-stage lung or liver cancer

Abstract: Vγ9Vδ2 T cells are promising candidates for cellular tumor immunotherapy. Due to their HLA-independent mode of action, allogeneic Vγ9Vδ2 T cells can be considered for clinical application. To apply allogeneic Vγ9Vδ2 T cells in adoptive immunotherapy, the methodology used to obtain adequate cell numbers with optimal effector function in vitro needs to be optimized, and clinical safety and efficacy also need to be proven. Therefore, we developed a novel formula to improve the expansion of peripheral γδ T cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
183
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 54 publications
2
183
0
Order By: Relevance
“…Cis-platinum has been used as clinical therapy drug against breast cancer for many years, however, its severe side effects limited the treatment efficacy clinically. V9V2 T cell has been increasingly recognized as new therapy strategy for cancer, since this cell could regulate immune function of the patients [15,16,19]. Immunotherapy including immune cells-based approach has become a new frontier of tumor therapy, but chemotherapy drug-based traditional protocol still plays an important role clinically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cis-platinum has been used as clinical therapy drug against breast cancer for many years, however, its severe side effects limited the treatment efficacy clinically. V9V2 T cell has been increasingly recognized as new therapy strategy for cancer, since this cell could regulate immune function of the patients [15,16,19]. Immunotherapy including immune cells-based approach has become a new frontier of tumor therapy, but chemotherapy drug-based traditional protocol still plays an important role clinically.…”
Section: Discussionmentioning
confidence: 99%
“…V9V2 T cell belongs to one subset of human peripheral  T cell, one major component of T lymphocytes (the other is αβ T cell). V9V2 T cells showed promising clinical value because of the potent anti-tumor activity [15][16][17], thus could be developed into a new strategy [13,15,16,[18][19][20] for breast cancer immunotherapy. For example, V9V2 T cells could inhibit breast cancer cell proliferation by regulating crucial molecules related to cell survival and apoptosis [21]; V9V2 T cells exerted promising breast tumor inhibition activity in the context of zoledronic acid pre-treatment [22]; notably, clinical Phase I trial study on breast cancer patients revealed that sustained population of V9V2 T cells were positively correlated with sound prognosis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Cis-platinum has been used as clinical therapy drug against breast cancer for many years, however, its severe side effects limited the treatment efficacy clinically. Vγ9Vδ2 T cell has been increasingly recognized as new therapy strategy for cancer, since this cell could regulate immune function of the patients [ 16 , 17 , 20 ]. Immunotherapy including immune cells-based approach has become a new frontier of tumor therapy, but chemotherapy drug-based traditional protocol still plays an important role clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of γδ T cell isolation and culture had been described in detail in previous reports [ 16 , 17 , 26 , 27 ]. Briefly, the peripheral blood was collected from healthy donors, then peripheral blood monocyte cells (PBMCs) were isolated using the Ficoll-Paque centrifugation protocol, following by culturing PBMCs in RPMI-1640 culture medium supplemented with 10% fetal bovine serum (FBS), IL-2 (5 ng/ml) and zoledronate (10 nM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation